2009
DOI: 10.1097/mcc.0b013e32832e0669
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complications after major surgery

Abstract: Postoperative respiratory complications may have significant deleterious consequences. Increasing the understanding of the underlying causes of respiratory complications and developing early treatment strategies will likely provide improved benefits. To date, early treatment with prophylactic or therapeutic continuous positive airway pressure has proved beneficial in an abdominal surgical patient population; however, the efficacy in a general population remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 70 publications
3
56
0
9
Order By: Relevance
“…Despite technical improvements and advances in perioperative care, major abdominal operations are still associated with a high rate of severe complications, long‐term disability, and health and social costs3, 4, 5, 6, 7. Moreover, the likelihood of successfully rescuing patients from surgery‐related morbidity is still unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Despite technical improvements and advances in perioperative care, major abdominal operations are still associated with a high rate of severe complications, long‐term disability, and health and social costs3, 4, 5, 6, 7. Moreover, the likelihood of successfully rescuing patients from surgery‐related morbidity is still unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Patients on NHF had significantly fewer desaturations and succeeded more in their allocated therapy, with less need for NIV or intubation, although respiratory (SpO 2 , respiratory rate and forced expiratory volume in 1 s) and cardiovascular (systolic and diastolic arterial pressure and heart rate) variables did not differ between groups. Positive airway pressure, enabling the recruitment of atelectatic lung areas, along with facilitation of mucociliary clearance by the heated and humidified gas administered by NHF, were the possible key features that improved overall treatment effectiveness in both studies [25,45], given that atelectasis is the more common respiratory complication after surgery, presenting in 90% of patients undergoing general anaesthesia [42]. The specific mechanisms of benefits of NHF on post-surgical respiratory complications were studied further by CORLEY et al [5] and it was found that NHF compared to low-flow oxygen on post-cardiac surgery patients significantly increased mean airway pressure by 3.0 cmH 2 O, tidal volume by 10.5% and EELV by 25.6%, regardless of whether they breathed with the mouth open or closed.…”
Section: No Benefitmentioning
confidence: 99%
“…Post-extubation following surgery Benefit Respiratory complications play a significant role after major surgery, and can determine morbidity and mortality and substantially increase healthcare cost [42,43]. Traditionally, low-and high-flow oxygen systems have been used to reverse post-surgical respiratory complications.…”
Section: No Benefitmentioning
confidence: 99%
“…Atelektazi gelişimi akciğer kompliyansında azalmayla birlikte ventilasyon-perfüzyon bozukluğu, şantlar, gaz değişi-minde bozulma ve pulmoner vasküler dirençte artma sonucu ciddi hipoksemilere neden olur. Ayrıca, oksijenizasyonda bozulma ve akciğer permeabilitesinde artma sonucu akut akciğer hasarına neden olabilir (13 na geçişte artış sonucu infeksiyonlara zemin hazırlar (14). Atelektazi dışında koroner arter by-pass cerrahisi veya akciğer rezeksiyonları sonucu doğrudan akciğer hasarına bağlı oluşan akut akciğer hasarı ve akut solunum sıkıntısı sendromu (ARDS), pulmoner emboli, çe-şitli ilaçlar veya inflamatuvar mediyatörler sonucu oluşan bronkospazm, aspirasyon pnömonisi, pnömoto-raks, akciğer ödemi ve frenik sinir zedelenmesine bağ-lı gelişen diyafram disfonksiyonu, POSY'nin diğer nedenleri arasında sayılabilir (11,13) (Şekil 1).…”
unclassified